Factors affecting staff support of a voluntary nonlead ammunition outreach program. Issue 1 (2nd February 2022) - Schulz, John H.; Wilhelm Stanis, Sonja A.; Li, Christine Jie; Morgan, Mark; Webb, Elisabeth B.
Abstract: Lead poisoning from ingestion of bullet fragments in gut piles and unretrieved deer carcasses continues to cause mortality in bald eagles. To address this issue, the Midwest region of the U.S. Fish and Wildlife Service (USFWS) initiated an outreach program during 2016–2018 encouraging hunters to voluntarily use nonlead ammunition while deer hunting on National Wildlife Refuges (NWRs). We conducted a survey to assess this program using seven factors that might influence USFWS staff support for the nonlead outreach program: innovativeness, lead exposure to bald eagles, availability of training and outreach materials, satisfaction with program implementation, importance of informational materials, and if they were a deer hunter. Multiple linear regression showed attitudes toward eagles' lead risk and importance of informational materials had the strongest effect on program support, followed by an individual's innovativeness. Although previous studies have focused on influencing hunters' nonlead use, our findings show staff attitudes and perceptions about nonlead strongly affect program support and ultimately program outcomes.